Moving toward the future of policing - Treverton, Gregory F. (RAND Corporation monograph series, 2011)
Some police forces believe that 20 years from now they will operate much as they do today, but advances in technology and operating concepts are driving significant changes in day-to-day police operations. This book explores potential visions of the future of policing, based on the drivers of jurisdiction, technology, and threat, and includes concrete steps for implementation. This analysis is based on a review of policing methods and theories from the 19th century to the present day. Recommendations include educating personnel and leaders to build internal support for change, transitioning to shared technical platforms, and leveraging winning technologies. Because criminals will also use new technology that becomes available, the key to the future of policing will not be the technology itself; it will be the ways in which police forces adapt the technology to their needs